Prospective of an Inland Waterway System of Shipping Canals in Skikda (Algeria) - Ghennaï, Amira (2023)
Sustainable development projects require careful balancing of economic interests and ecological needs. The case of Skikda, a city in northeast Algeria, located on the Mediterranean coast, illustrates the challenges connected with such a development. The ancient city coexists with a young hydrocarbon port and industrial pole that serves as a transfer hub in the flow of petroleum between hinterland and sea. The installation of the port and petrochemical refining plants on the banks of the estuary of the Safsaf River presents many challenges to local citizens and the ecosystem, including pollution of the water system, groundwater, and river water, and damage to the area’s ancient heritage. This study argues that we need new and less polluting forms of intermodality between hinterland and seaport to make urban mobility more sustainable. It asks whether and how the existing rivers and wadis (river channels that are dry except during rainy periods) can be transformed into artificial canals for river navigation to improve the transport fluidity and sustainability of Skikda. To answer this question, the study adopts a prospective approach using the MICMAC scenario method. This approach entails, first, presenting and evaluating the potentialities of the existing rivers of Skikda using QGIS, and second, discussing and proposing scenarios for transforming these rivers into urban waterways, that is, artificial canals for inland navigation. The prospect of inland waterway transport in Skikda may be a radical scenario, yet, despite its hydraulic capacity and advantages, this system is not receiving attention in Algeria. We suggest that water transport can breathe sustainable blue life into a vulnerable industrial port city, transforming its challenges into opportunities.